2014
DOI: 10.1002/rob.21562
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Structure Filter for Sensor Registration from Unstructured Terrain

Abstract: Correct registration of vehicle‐mounted sensors is a fundamental prerequisite for the perception capabilities required for automation. However, the use of a standard marker or artificial‐feature‐based approaches is often infeasible in environments that do not allow for additional infrastructure. This paper presents a method for sensor registration that overcomes this limitation by utilizing the geometric structure of the terrain surrounding the sensor platform. The method determines the information content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The Velodyne HDL-64E has a sensor measurement uncertainty (1σ sensor ) of 20 mm (Velodyne LiDAR Inc, 2008), hence v k ∼ N (0, σ 2 sensor ). A previous study in registering this sensor to mining platforms found that the registration parameters could be recovered with 1σ uncertainties of approximately 10 mm and 1 mrad in position and orientation respectively (Phillips et al, 2014). The deviation to sensor pose is drawn from this parameter covariance, i.e.…”
Section: Assessing Univariate Measurement Likelihoodmentioning
confidence: 99%
See 2 more Smart Citations
“…The Velodyne HDL-64E has a sensor measurement uncertainty (1σ sensor ) of 20 mm (Velodyne LiDAR Inc, 2008), hence v k ∼ N (0, σ 2 sensor ). A previous study in registering this sensor to mining platforms found that the registration parameters could be recovered with 1σ uncertainties of approximately 10 mm and 1 mrad in position and orientation respectively (Phillips et al, 2014). The deviation to sensor pose is drawn from this parameter covariance, i.e.…”
Section: Assessing Univariate Measurement Likelihoodmentioning
confidence: 99%
“…Scans typically have in the order of 20-30 thousand useful range measurements. The sensor is registered to the machine house using methods 2 real time kinematic global navigation satellite system/inertial measurement unit solution 130 5.3 Five challenges in applying iterative closest point for truck and dipper pose estimation described in Phillips et al (2014). Typical data from a scan is shown in Fig.…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The Velodyne LiDAR is registered to the navigation solution using the method described in Phillips et al (2014) and has been assessed as being precise to 0.01 m and 0.05…”
Section: Measurement Datamentioning
confidence: 99%
“…Surfaces fitted to the quasi point clouds are matched using a generalized GaussMarkov model, minimizing the sum of squared Euclidean distances between surfaces. The approach is claimed to improve robustness although it suffers in two respects: (i) range errors associated with high intensity returns tend to be larger than those low intensity returns (Phillips et al, 2014); and (ii) intensity measurements are subject to variation, depending for instance, on the angle of incidence of the LiDAR ray to the surface. Hebel and Stilla (2007) use intensity information to constrain the correspondence estimation.…”
Section: Features In Point Cloud Datamentioning
confidence: 99%